COVID-19 therapy and vaccination: a clinical narrative review - Siddharth Chinta; Miguel Rodriguez-Guerra; Mohammed Shaban; Neelanjana Pandey; Maria Jaquez-Duran; Timothy J Vittorio (BioExcel Publishing Ltd, 2023)
The SARS-CoV-2 pandemic is the most globally impacting health issue our world has faced over the last century. As of January 7, 2022, around 300 million cases have been reported worldwide, with over 5 million deaths. The SARS-CoV-2 infection causes a hyperactive host immune response leading to an excessive inflammatory reaction with the release of many cytokines - cytokine storm - commonly noticed in acute respiratory distress syndrome, sepsis and fulminant multiorgan failure. Since the beginning of the pandemic, the scientific medical community has worked on therapeutic procedures that interfere with the exaggerated immune response. Thromboembolic complications are widespread in patients who are critically ill with COVID-19. Anticoagulant therapy was initially considered a cornerstone in hospitalized patients and even in the early post-discharge period; however, later trials have aborted the clinical benefits except for suspicion of or confirmed thrombosis. Immunomodulatory therapies are still crucial in moderate to severe COVID-19. Immunomodulator therapies include various medications from steroids to hydroxychloroquine, tocilizumab and Anakinra. Anti-inflammatory agents, vitamin supplements and antimicrobial therapy had initial encouraging evidence, but there are limited data to review. Convalescent plasma, immunoglobulins, eculizumab, neutralizing IgG1 monoclonal antibodies and remdesivir have positively impacted inpatient mortality and hospital length of stay. Eventually, wide population vaccination was proven to be the best tool to overcome the SARS-CoV-2 pandemic and help humanity return to regular life. Many vaccines and various strategies have been used since December 2020. This review discusses how the SARS-CoV-2 pandemic has progressed and surged, and summarizes the safety and efficacy of the most used therapies and vaccines in the light of recent evidence.